2018
DOI: 10.1002/etc.4176
|View full text |Cite
|
Sign up to set email alerts
|

Ecotoxicological Assessment of Immersion Samples from Facade Render Containing Free or Encapsulated Biocides

Abstract: To protect house facades from fouling by microorganisms, biocides can be added to a render or paint before it is applied. During driving rain events, these biocides gradually leach out and have the potential to pollute soil or aquatic ecosystems. We studied the leaching behavior of biocides and toxicity of leachates from renders with either free or encapsulated biocides. Both render types contained equal amounts of terbutryn, 2-octyl-3(2H)-isothiazolinone (OIT), and 4,5-dichloro-2-n-octyl-4-isothiazolino-3-one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…In recent years, biocidal substances in the aquatic environment have received an increasing attention because of (i) their many uses especially in urban areas (Bester et al 2008;Bollmann et al 2014b;Paijens et al 2020;Wieck et al 2018), (ii) their transfer into the aquatic environment via wastewater or stormwater discharges (Bollmann et al 2014a;Burkhardt et al 2011;Juksu et al 2019;Wicke et al 2015), and (iii) their negative effect on aquatic organisms (Mohr et al 2008;Vermeirssen et al 2018). Indeed, biocides are toxic and may cause long-term adverse effects to aquatic ecosystems even at low concentrations, such as endocrine disruption in zebrafish larvae (Jiang et al, 2015) or behavioural disturbance in zebrafish embryos (Andrade et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, biocidal substances in the aquatic environment have received an increasing attention because of (i) their many uses especially in urban areas (Bester et al 2008;Bollmann et al 2014b;Paijens et al 2020;Wieck et al 2018), (ii) their transfer into the aquatic environment via wastewater or stormwater discharges (Bollmann et al 2014a;Burkhardt et al 2011;Juksu et al 2019;Wicke et al 2015), and (iii) their negative effect on aquatic organisms (Mohr et al 2008;Vermeirssen et al 2018). Indeed, biocides are toxic and may cause long-term adverse effects to aquatic ecosystems even at low concentrations, such as endocrine disruption in zebrafish larvae (Jiang et al, 2015) or behavioural disturbance in zebrafish embryos (Andrade et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Only scarce studies assess the toxicity of the leachates though this would be a relevant tool for assessing potential environmental impact (Bandow et al 2018). For instance, Vermeirssen et al (2018) conducted ecotoxicity test on leachates and demonstrated that combining standardized leaching tests with standardized bioassays is a valuable tool to assess the environmental risk of biocide releases from façade renders and to rank the different materials according to potential ecotoxicity.…”
Section: Small-scale Emissionsmentioning
confidence: 99%
“…Finally, ITs are very frequently used to prevent the biodeterioration of buildings, roofs, stones, and facades. For example, ITs and especially OIT and its derivative the 4,5-dichloro-2octyl-2H-isothiazol-3-one (DCOIT, CAS: 64359-81-5) are utilized in paints that are sold to protect house facades (Vermeirssen et al, 2018), such as Lichenicida 468 (Bresciani) (Favero-Longo et al, 2017) or Algi 201 (Algimouss Pro, ITs concentration 0.45%). They can be employed alone or combined with other antifouling compounds, such as quaternary ammonium compounds (see below).…”
Section: Isothiazolinonesmentioning
confidence: 99%